Cytosolic streaming in vegetative mycelium and aerial structures of Aspergillus niger - Bleichrodt, R. (CBS Fungal Biodiversity Centre, 2013)
Aspergillus niger forms aerial hyphae and conidiophores after a period of vegetative growth. The hyphae within the mycelium of A. niger are divided by septa. The central pore in these septa allows for cytoplasmic streaming. Here, we studied inter- and intra-compartmental streaming of the reporter protein GFP in A. niger. Expression of the gene encoding nuclear targeted GFP from the gpdA or glaA promoter resulted in strong fluorescence of nuclei within the vegetative hyphae and weak fluorescence in nuclei within the aerial structures. These data and nuclear run on experiments showed that gpdA and glaA are higher expressed in the vegetative mycelium when compared to aerial hyphae, conidiophores and conidia. Notably, gpdA or glaA driven expression of the gene encoding cytosolic GFP resulted in strongly fluorescent vegetative hyphae and aerial structures. Apparently, GFP streams from vegetative hyphae into aerial structures. This was confirmed by monitoring fluorescence of photo-activatable GFP (PA-GFP). In contrast, PA-GFP did not stream from aerial structures to vegetative hyphae. Streaming of PA-GFP within vegetative hyphae or within aerial structures of A. niger occurred at a rate of 10–15 μm s(-1). Taken together, these results not only show that GFP streams from the vegetative mycelium to aerial structures but it also indicates that its encoding RNA is not streaming. Absence of RNA streaming would explain why distinct RNA profiles were found in aerial structures and the vegetative mycelium by nuclear run on analysis and micro-array analysis.